Subjective Health Complaints in Women Famers Exposed to Pesticides in Agricultural Area - Imelda Gernauli Purba; Haryoto Kusnoputranto (School of Postgraduate Studies, Diponegoro Univer, 2025)
Pesticides are chemicals that are increasingly used particularly in agriculture to control plant pests. While pesticides offers benefits they also cause adverse effects on humans, especially if not handled properly. Women in agricultural areas exposed to pesticides are at risk of developing health problems related to pesticide exposure, which are often related to their involvement in agricultural activities such as spraying, mixing pesticides, washing spraying equipment and clothing. The research aims to analyse the risk factors for subjective health complaints due to pesticide exposure in female farmers. The observational study employed a cross-sectional approach. The study population comprised female farmers exposed to pesticides residing in Sekayu District, Musi Banyuasin South Sumatra, Indonesia. A sample size of 136 was obtained through Cluster Sampling. Primary data were collected through interviews and observations using questionnaires and checklists. Data were analysed using the Chi-Square Test. The results indicated that female farmers reported a range of subjective health complaints including fatigue, anxiety, headache, blurred vision, nausea, decreased appetite, muscle weakness, and muscle spasms. Several variables were associated with subjective health complaints including age (p=0.05), working period (p=0.002), number of types of pesticides (p=0.000), and storage method of pesticides (p=0.021). Female farmers should limit their exposure to pesticides through reducing the length of contact with pesticides, avoiding the mixing of different types of pesticides, and storing pesticides according to the storage instructions.